2017
DOI: 10.1016/j.tics.2016.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Emojis: Insights, Affordances, and Possibilities for Psychological Science

Abstract: We live in a digital society that provides a range of opportunities for virtual interaction. Consequently, emojis have become popular for clarifying online communication. This presents an exciting opportunity for psychologists, as these prolific online behaviours can be used to help reveal something unique about contemporary human behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(95 citation statements)
references
References 8 publications
2
86
0
1
Order By: Relevance
“…Moreover, Massaro's perceptual experiments (Massaro & Egan, 1996;Massaro, 1998), which manipulated the degree of conflicting audio and visual speech information, suggested that humans rely on both channels to understand the signal, giving more weight to the channel with the most reliable information. If we remove these additional communicative acts of the body, the comprehension of language is often impaired: 'emojis', for instance, were invented to remove the ambiguity in text messages (Lo, 2008;Kaye, Malone & Wall, 2017). In light of the universal use of bodily signals and cues to complement our words and refine our messages (e.g.…”
Section: Introduction: Language Evolution and The Comparative Apprmentioning
confidence: 99%
“…Moreover, Massaro's perceptual experiments (Massaro & Egan, 1996;Massaro, 1998), which manipulated the degree of conflicting audio and visual speech information, suggested that humans rely on both channels to understand the signal, giving more weight to the channel with the most reliable information. If we remove these additional communicative acts of the body, the comprehension of language is often impaired: 'emojis', for instance, were invented to remove the ambiguity in text messages (Lo, 2008;Kaye, Malone & Wall, 2017). In light of the universal use of bodily signals and cues to complement our words and refine our messages (e.g.…”
Section: Introduction: Language Evolution and The Comparative Apprmentioning
confidence: 99%
“…It would therefore be good for future research to also test alternative ways of expressing emotions (e.g., verbally or nonverbally by studying facial expressions). Related to this, the generalizability of our findings might be tested in less anonymous settings, such as conversations by telephone or email that allow for other types of communication (see, e.g., the emerging research on using emojis to communicate emotions in written texts; Glikson, Cheshin, & Van Kleef, in press; Kaye, Malone, & Wall, ). Van Kleef () recently noted that interpersonal effects of emotions, including the signaling value of emotion communications, tend to be quite similar across expressive modalities.…”
Section: Discussionmentioning
confidence: 99%
“…These ideograms have evolved beyond facial expressions, and are increasingly used on digital platforms to demonstrate concepts and ideas. As a Japanese word meaning "picture character", emojis were initially created at the end of the twentieth century in order to improve and simplify digital messages [1,2]. They are increasingly used as a new language worldwide, conveying nonverbal communication cues and, in the case of the latter, substituting for the face-to-face conditions, and proving to exert a direct effect on readers' moods [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…These pictographs became so popular that the Oxford dictionary announced the "face with tears of joy" ( ) emoji as the 2015 word of the year [7]. More than 90% of the online users employ emojis to communicate complex concepts more effectively while using less words [2].…”
Section: Introductionmentioning
confidence: 99%